Association between lncRNA ANRIL genetic variants with the susceptibility to ischemic stroke: From a case-control study to meta-analysis. Issue 11 (19th March 2021) - Wang, Qianwen; Zhao, Jingjing; Chang, Hongtao; Liu, Xu; Zhu, Ruixia
Abstract: Background: Recent studies have reported that lncRNA (long noncoding RNAs) antisense non-coding RNA in the INK4 locus (ANRIL) plays important roles in the development of atherosclerosis through regulating cell apoptosis, proliferation, and adhesion. GWAS (genome-wide association studies) identified common genetic variants within ANRIL could confer risk of ischemic stroke (IS) in southern Sweden. Methods: We performed a case-control study, including 567 IS patients and 552 healthy controls from unrelated northern Chinese Han population, aiming to explore the association between lncRNA ANRIL rs2383207, rs4977574 polymorphisms and the risk of IS. Subsequently we implemented a meta-analysis to further assess the relationship of these variants and the disease. Results: In our case-control study, no significant associations were observed in all models between above 2 polymorphisms and IS. Next in our subgroup analysis, we detected significant association between GA genotype of rs4977574 and the increased risk of LAA-IS (large-artery atherosclerotic ischemic stroke), similar elevated risk also appeared in the GG + GA genotype under the dominant model ( P  = .048, OR = 1.385, 95% CIs 1.002–1.914; P  = .040, OR = 1.378, 95% CIs 1.015–1.872, respectively). As for rs2383207, negative results were obtained under all models and subgroups. Our meta-analysis showed a significant association between rs4977574 polymorphism and IS risk in allele model (G vs A P  = .002, OR = 1.137, 95% CIs 1.048–1.234); with respect to rs2383207 polymorphism, no significant association between that and the risk of IS was detected under the dominant model (GA + AA vs GG, P  = .061, OR = 0.923, 95% CIs 0.849–1.004), or recessive model (AA vs GA + GG, P  = .656, OR = 0.972, 95% CIs 0.858–1.101), or allele model (A vs G, P  = .326, OR = 0.952, 95% CIs 0.863–1.050). Likewise, no significant association between rs2383207 and IS was found in different stoke subtypes ( P  > .05). Conclusions: Our findings indicated G allele of lncRNA ANRIL rs4977574 could increase the risk of IS, and the variant may be associated with susceptibility to LAA-IS in Chinese Han population. Abstract : Supplemental Digital Content is available in the text